Engineered TAL Effector modulators for the large-scale gain-of-function screening. Issue 14 (17th June 2014) - Zhang, Hanshuo; Li, Juan; Hou, Sha; Wang, Gancheng; Jiang, Mingjun; Sun, Changhong; Hu, Xiongbing; Zhuang, Fengfeng; Dai, Zhifei; Dai, Junbiao; Xi, Jianzhong Jeff
Abstract: Recent effective use of TAL Effectors (TALEs) has provided an important approach to the design and synthesis of sequence-specific DNA-binding proteins. However, it is still a challenging task to design and manufacture effective TALE modulators because of the limited knowledge of TALE–DNA interactions. Here we synthesized more than 200 TALE modulators and identified two determining factors of transcription activity in vivo : chromatin accessibility and the distance from the transcription start site. The implementation of these modulators in a gain-of-function screen was successfully demonstrated for four cell lines in migration/invasion assays and thus has broad relevance in this field. Furthermore, a novel TALE–TALE modulator was developed to transcriptionally inhibit target genes. Together, these findings underscore the huge potential of these TALE modulators in the study of gene function, reprogramming of cellular behaviors, and even clinical investigation.